An attempt to determine the focus of the strategy of development of physical culture and sport in rural areas of Ukraine by expert evaluation - Dorofieieva, Tеtіana (VIREF Revista de Educación Física, 2022)
Context: we put forward the hypothesis that conducting an expert survey with the involvement of experienced practitioners, bearers of ideas about the state and conditions of existence of the sphere of sport in newly created Ukraine united territorial communities, will allow us to highlight those factors/factors, accounting of which will allow determining some of the critical problems, which solution will form the basis of the necessary and expected strategy. Objective: to determine the basic approaches to developing physical culture and sport in rural areas of Ukraine by expert evaluation method. Methods: an author's questionnaire was developed, the content of which was based on the questions in the regional strategy of healthy lifestyles in the united territorial communities, the authors of which were the experts of the Department of Youth and Sports of Dnipropetrovsk Regional State Administration. The survey involved 21 experienced experts of the Dnipropetrovsk regional branch of the All-Ukrainian physical culture and sports society "Kolos" aged from 32 to 72 years, 14 men and seven women. The survey of experts was conducted in December 2020 by answering the author's questionnaire. Results: the received answers to the questions of the author's questionnaire noted the incredible diversity, scattered, and not coordinated assessments. That allowed the experts to highlight the main problems, the solution of which should be the basis of the strategy. Conclusion: Therefore, the proposed survey does not allow identifying the central problems on which a policy for developing physical culture and sports in the town can be suggested.